Carcass characteristics and cost benefits of two broiler strains as affected by duration of feed withdrawal at finisher phase - Olawumi, S. O.; I. Osagiri, B. O. Oyewole, A. A. Okpe, C. Amana (Journal of Scientific Agriculture, 2019)
The present study was undertaken to examine the before and post-slaughter characteristics of two broiler strains under feed withdrawal regime during the hot weather conditions. 180 day-old broiler chicks comprising 90 chicks each of Arbor Acre and Ross 308 were procured from reputable hatchery, and were raised for four weeks before being distributed randomly to three groups of feed withdrawal regime. The treatments are: T1= ad libitum (control), T2= 8-12noon feeding (morning) and T3= 12noon-4pm feeding (afternoon). Each treatment was replicated thrice with 10 birds per replicate. At 49th day, three birds per treatment were randomly taken after starving them overnight for carcass evaluation. Analysed data showed that there was no significant effect of strain on live weight, carcass and non-carcass traits regardless of feed restriction employed. But Arbor Acre recorded higher net profit than Ross308 in terms of cost of production on strain basis. With regard to duration of feed withdrawal, dressed weight, eviscerated weight, carcass weight and back weight were significantly affected by the feeding regime imposed on the birds. Birds on ad libitum and afternoon feeding groups had higher and superior mean values to morning group. This implies that feeding birds in the afternoon under favourable conditions and improved management practices is beneficial and economically viable and profitable.